2021
DOI: 10.1155/2021/5906855
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of a Care Bundle Combined with Continuous Positive Airway Pressure in the Postanesthesia Care Unit on Rapid Recovery after Pulmonary Tumor Resection

Abstract: Objective. To study the effect of a care bundle combined with continuous positive airway pressure (CPAP) in the postanesthesia care unit (PACU) on rapid recovery after pulmonary tumor resection. Methods. A total of 135 patients requiring anesthesia resuscitation after pulmonary tumor resection in our hospital from June 2020 to February 2021 were selected. They were randomly divided into three groups: the PACU experimental group, PACU control group, and operating room resuscitation (OR) group. Subsequently, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…Specifically, the patient's care bundle provides further optimized nursing services for patients ( 54 ). Therefore, compared with an individual one of practice measures, a better effect will achieve for the treatment and recovery of patients after combining all measures ( 55 ). Actually, studies have suggested that accurate and effective implementation of the care bundle significantly reduced the risk of SAP and improved the functional prognosis in stroke patients ( 52 , 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the patient's care bundle provides further optimized nursing services for patients ( 54 ). Therefore, compared with an individual one of practice measures, a better effect will achieve for the treatment and recovery of patients after combining all measures ( 55 ). Actually, studies have suggested that accurate and effective implementation of the care bundle significantly reduced the risk of SAP and improved the functional prognosis in stroke patients ( 52 , 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%